The genre of suffering in the 'ancient near eastern literature, the Hebrew bible, and in some examples of modern literature. - Middelkoop, Roeland (School of Languages and Literatures, 2023)
The aim of this thesis is to compare works of drama regarding the suffering of the human being in the context of life and literature and in relation to the issue of justice, which revolves around the impact of Justice, Humanity and God. My aim is to look at the development of the genre of suffering starting with the Ancient Near Eastern Literature, to define the genre in its development and to characterise its features in the various literatures discussed, especially with respect to the Book of Job. The book of Job is well known for its input in world literature on the theme of suffering. It is therefore important to trace the genre of suffering from its literary origins in the ancient near east and from there to Job. Hence, I will look at ancient works on suffering from Sumeria, from Babylon and from Egypt, and then at the book of Job. I will compare and examine the differences in their approaches and their understanding of God and of justice.